Structure of the dopamine D2 receptor in complex with the antipsychotic drug spiperone - Im, Dohyun; Inoue, Asuka; Fujiwara, Takaaki; Nakane, Takanori; Yamanaka, Yasuaki; Uemura, Tomoko; Mori, Chihiro; Shiimura, Yuki; Kimura, Kanako Terakado; Asada, Hidetsugu; Nomura, Norimichi; Tanaka, Tomoyuki; et al. (Nature communications, 2020)
In addition to the serotonin 5-HT 2A receptor (5-HT 2A R), the dopamine D 2 receptor (D 2 R) is a key therapeutic target of antipsychotics for the treatment of schizophrenia. The inactive state structures of D 2 R have been described in complex with the inverse agonists risperidone (D 2 R ris ) and haloperidol (D 2 R hal ). Here we describe the structure of human D 2 R in complex with spiperone (D 2 R spi ). In D 2 R spi , the conformation of the extracellular loop (ECL) 2, which composes the ligand-binding pocket, was substantially different from those in D 2 R ris and D 2 R hal , demonstrating that ECL2 in D 2 R is highly dynamic. Moreover, D 2 R spi exhibited an extended binding pocket to accommodate spiperone’s phenyl ring, which probably contributes to the selectivity of spiperone to D 2 R and 5-HT 2A R. Together with D 2 R ris and D 2 R hal , the structural information of D 2 R spi should be of value for designing novel antipsychotics with improved safety and efficacy. The dopamine D 2 receptor (D 2 R) is a GPCR and an important drug target for schizophrenia treatment. Here, the authors present the crystal structure of human D 2 R in complex with the antipsychotic drug spiperone, which is of interest for designing antipsychotics with improved receptor selectivity.